(3X+7)(5X-3)=0

Simple and best practice solution for (3X+7)(5X-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3X+7)(5X-3)=0 equation:


Simplifying
(3X + 7)(5X + -3) = 0

Reorder the terms:
(7 + 3X)(5X + -3) = 0

Reorder the terms:
(7 + 3X)(-3 + 5X) = 0

Multiply (7 + 3X) * (-3 + 5X)
(7(-3 + 5X) + 3X * (-3 + 5X)) = 0
((-3 * 7 + 5X * 7) + 3X * (-3 + 5X)) = 0
((-21 + 35X) + 3X * (-3 + 5X)) = 0
(-21 + 35X + (-3 * 3X + 5X * 3X)) = 0
(-21 + 35X + (-9X + 15X2)) = 0

Combine like terms: 35X + -9X = 26X
(-21 + 26X + 15X2) = 0

Solving
-21 + 26X + 15X2 = 0

Solving for variable 'X'.

Factor a trinomial.
(-7 + -3X)(3 + -5X) = 0

Subproblem 1

Set the factor '(-7 + -3X)' equal to zero and attempt to solve: Simplifying -7 + -3X = 0 Solving -7 + -3X = 0 Move all terms containing X to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3X = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3X = 0 + 7 -3X = 0 + 7 Combine like terms: 0 + 7 = 7 -3X = 7 Divide each side by '-3'. X = -2.333333333 Simplifying X = -2.333333333

Subproblem 2

Set the factor '(3 + -5X)' equal to zero and attempt to solve: Simplifying 3 + -5X = 0 Solving 3 + -5X = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5X = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5X = 0 + -3 -5X = 0 + -3 Combine like terms: 0 + -3 = -3 -5X = -3 Divide each side by '-5'. X = 0.6 Simplifying X = 0.6

Solution

X = {-2.333333333, 0.6}

See similar equations:

| t(4t+5)(4t-5)=0 | | X+Y+(X+9)=30 | | -3(3y-6)+2(2y+8)= | | 18x^2-x-254779=0 | | 6.3+6.7s=-3.9 | | v^2-11v-2=0 | | M=15x-5 | | ydx+(x^3+x^3y^2)dy=0 | | 4c+d-10c+4d= | | -6.3+6.7s=-3.9 | | 9(3+6)-(2*18)= | | 3(x-5)-8x=10x+75 | | 7/9r=5/7 | | 15x-12=-8x | | 10x^2+20x-70=10 | | 5.1/3 | | z^6y^3/z^6y^4 | | (n+1)=15n | | 1X+5Y+20X=171 | | 2x^2+11x-3219=0 | | x^2-7x-147=0 | | 184=120+6t+0.04t^2 | | 4tanx-8=8 | | 20s^2-44s-48=0 | | 19n-20=36-9n | | 8b-4=12 | | 10X-27+5x-2x=x+8-5 | | 3/a^-9b | | 2(x+3)-(-5)(x-1)=0 | | (x+2)(6x^3-29x^2)(37x-12)=0 | | 8+17x=18x+2 | | (6x^3-29x^2)(37x-12)=0 |

Equations solver categories